(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Bangladesh is endowed with a vast expanse of inland open waters characterized by rivers, canals, natural and man-made lakes, freshwater marshes, estuaries, brackish water impoundments and floodplains. The potential fish resources resulting from these are among the richest in the world; in production, only China and India outrank Bangladesh. The inland fish diversity of is attributed to the habitats created by the Bengal Delta wetlands and the confluence of the Brahmaputra, Ganges and Jamuna rivers that flow from the Himalayan Mountains into the Bay of Bengal. There are, however, serious concerns surrounding the slow decline in the condition of open water fish stocks which have been negatively impacted upon through a series of natural and anthropogenic induced changes including large scale abstraction of water for irrigation and the construction of water barrages and dams, human activity resulting in the overexploitation of stocks, the unregulated introduction of exotic stocks and pollution from industry. Also, natural phenomena, regular flooding etc. cause rivers to continually change course creating complications of soil erosion or over siltation of waterways. As a consequence, many Bangladeshi species are either critically endangered or extinct. Aquaculture has increasingly been playing a major role in total fish production of the country and presently more than half of the total production comes from aquaculture. The sector provides living and livelihood for more than 11% people of the country. If the available resources are used sustainably with proper technological assistance, fish produced from aquaculture would efficiently meet the protein demand of growing population of the country. The needs of Bangladeshs poor fisher community to eat what they catch and lack of a legal legislative framework means the situation can only worsen. Hope, however, is offered through several new conservation initiatives including the establishment of fish sanctuaries at strategic points in rivers and floodplains, concerted breeding programmes and the maintenance of captive stocks and cryogenically stored materials. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22375 Res. Agric., Livest. Fish.1(1): 109-126, Dec 2014